2018
DOI: 10.4314/bajopas.v10i1.68s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heavy metals in beans and some beans product from some selected markets in Katsina State Nigeria

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 1 publication
(2 reference statements)
13
5
3
Order By: Relevance
“…But these values are higher than the range (0.002 to 0.004 mg/kg) reported by Edem et al [33] in Wheat flours in 2009. The reported Cd values in the present study are lower than that reported for various beans samples from Europe, Asia and parts of West Africa [24], reported in a study for the Cadmium concentration range for both unprocessed and processed bean samples from Katsina state Nigeria [21] and for locust beans from Odo-Ori market Iwo, Nigeria [34]. The values are also lower than those obtained by Okoye et al, [29] in Cereals in Southeastern Nigeria (0.007 to 0.23 mg/kg) in 2009, Ahmed and Mohammed [28] in Cereal products (0.091-0.143 mg/kg) in 2005, Orisakwe et al [35] in Owerri (0.00 to 0.24mg/kg) in 2012 and Dahiru et al, [26] in Kano (0.11 to 0.28 mg/kg) in 2013.…”
Section: Resultscontrasting
confidence: 86%
See 4 more Smart Citations
“…But these values are higher than the range (0.002 to 0.004 mg/kg) reported by Edem et al [33] in Wheat flours in 2009. The reported Cd values in the present study are lower than that reported for various beans samples from Europe, Asia and parts of West Africa [24], reported in a study for the Cadmium concentration range for both unprocessed and processed bean samples from Katsina state Nigeria [21] and for locust beans from Odo-Ori market Iwo, Nigeria [34]. The values are also lower than those obtained by Okoye et al, [29] in Cereals in Southeastern Nigeria (0.007 to 0.23 mg/kg) in 2009, Ahmed and Mohammed [28] in Cereal products (0.091-0.143 mg/kg) in 2005, Orisakwe et al [35] in Owerri (0.00 to 0.24mg/kg) in 2012 and Dahiru et al, [26] in Kano (0.11 to 0.28 mg/kg) in 2013.…”
Section: Resultscontrasting
confidence: 86%
“…The mean values obtained for the heavy metal (Cr) is similar with the results of Gomaa et al [36] for Cr in cucumber (0.16 mg/kg) from Egypt and the mean Cr concentration for market sold beans from Katsina, Nigeria [21]. But the results are lower than the Cr concentrations reported for homegrown vegetables near a former chemical manufacturing facility in Tarnaveni Romania [25].…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations